Study on Effect of Ultrasonic Vibration on Grinding Force and Surface Quality in Ultrasonic Assisted Micro End Grinding of Silica Glass - Zhang Jianhua; Zhao Yan; Zhang Shuo; Tian Fuqiang; Guo Lanshen; Dai Ruizhen (Shock and Vibration)
Ultrasonic vibration assisted micro end grinding (UAMEG) is a promising processing method for micro parts made of hard and brittle materials. First, the influence of ultrasonic assistance on the mechanism of this processing technology is theoretically analyzed. Then, in order to reveal the effects of ultrasonic vibration and grinding parameters on grinding forces and surface quality, contrast grinding tests of silica glass with and without ultrasonic assistance using micro radial electroplated diamond wheel are conducted. The grinding forces are measured using a three-component dynamometer. The surface characteristics are detected using the scanning electron microscope. The experiment results demonstrate that grinding forces are significantly reduced by introducing ultrasonic vibration into conventional micro end grinding (CMEG) of silica glass; ultrasonic assistance causes inhibiting effect on variation percentages of tangential grinding force with grinding parameters; ductile machining is easier to be achieved and surface quality is obviously improved due to ultrasonic assistance in UAMEG. Therefore, larger grinding depth and feed rate adopted in UAMEG can lead to the improvement of removal rate and machining efficiency compared with CMEG.